Patterns of xanthogranulomatous reaction in salivary glands. Histomorphological spectrum and differential diagnosis - Agaimy, A.; Ihrler, S. (Pathologe, 2014)
Xanthogranulomatous inflammation is an uncommon subtype of chronic inflammatory processes that has been mainly reported in the kidneys, gallbladder and other less common sites. Due to the presence of tumefactive mixed inflammatory infiltrates with variable involvement of surrounding soft tissues, this benign condition is often mistaken for a malignancy on clinical examination. In the salivary glands xanthogranulomatous inflammation is rare and mainly represents reactive changes secondary to a preexisting lesion, in particular infarcted Warthin tumors as well as ruptured ductal cysts and other sialectatic ductal changes. A special type of xanthogranulomatous salivary gland disease is represented by the rare primary (idiopathic) xanthogranulomatous sialadenitis without identifiable predisposing parenchymal or ductal lesions. The histological differential diagnosis is mainly based on the dominant histological pattern and encompasses among others inflammatory pseudotumors of various etiologies (e.g. inflammatory myofibroblastic tumor, IgG4-related disease and sarcoidosis), neoplastic and paraneoplastic xanthogranulomatosis, malignant lymphoma and carcinoma with secondary xanthogranulomatous reactions. Thus, identification of the underlying lesion is necessary for correct classification and to avoid overlooking more serious neoplastic or autoimmune diseases.
EVALuna2:6581